Perkembangan Usaha Kerajinan Anyaman Bambu di Nagari Koto Baru Simalanggang Kecamatan Payakumbuh Tahun 1990-2022 - Utami, Silvia; Hardi, Etmi (Lembaga Yasin AlSys, 2024)
This research examines the development of woven bamboo craft businesses in Nagari Koto Baru Simalanggang, Payakumbuh District, 1990-2022. The research aims to discover the development of woven bamboo craft businesses in Nagari Koto Baru Simalanggang and its impact on the socio-economic life of the local community. The method used in this research is a historical method with four stages of research methods, namely heuristics, source criticism, interpretation and historiography. Based on the research results, it can be seen that the bamboo woven craft business in the village of Koto Baru Simalanggang, Payakumbuh District has existed for a long time, but the year it appeared is not certain. Woven bamboo crafts have developed in shape and model. In 1990, the form of woven bamboo crafts was still very simple. In 1995, the woven bamboo craft business began to improve and develop significantly. Woven bamboo crafts were initially introduced by Mom Desweni. The woven bamboo craft business is a business that has been passed down from generation to generation through non-official education route. Bamboo woven craft business can be used as the main job for craftsmen to fulfill their daily needs. Bamboo woven craft business has a big influence on the socio-economic life of bamboo woven craftsmen in Nagari Koto Baru Simalanggang. Level of Education, Level of social welfare , and the socio-economic life of craftsmen has improved significantly from the existence of this bamboo woven craft business.